Sensitivity of Aspergillus nidulans to the cellulose synthase inhibitor dichlobenil: insights from wall-related genes' expression and ultrastructural hyphal morphologies. - Gea Guerriero; Lucia Silvestrini; Michael Obersriebnig; Marco Salerno; Dietmar Pum; Joseph Strauss (PLoS ONE)
The fungal cell wall constitutes an important target for the development of antifungal drugs, because of its central role in morphogenesis, development and determination of fungal-specific molecular features. Fungal walls are characterized by a network of interconnected glycoproteins and polysaccharides, namely α-, β-glucans and chitin. Cell walls promptly and dynamically respond to environmental stimuli by a signaling mechanism, which triggers, among other responses, modulations in wall biosynthetic genes' expression. Despite the absence of cellulose in the wall of the model filamentous fungus Aspergillus nidulans, we found in this study that fungal growth, spore germination and morphology are affected by the addition of the cellulose synthase inhibitor dichlobenil. Expression analysis of selected genes putatively involved in cell wall biosynthesis, carried out at different time points of drug exposure (i.e. 0, 1, 3, 6 and 24 h), revealed increased expression for the putative mixed linkage β-1,3;1,4 glucan synthase celA together with the β-1,3-glucan synthase fksA and the Rho-related GTPase rhoA. We also compared these data with the response to Congo Red, a known plant/fungal drug affecting both chitin and cellulose biosynthesis. The two drugs exerted different effects at the cell wall level, as shown by gene expression analysis and the ultrastructural features observed through atomic force microscopy and scanning electron microscopy. Although the concentration of dichlobenil required to affect growth of A. nidulans is approximately 10-fold higher than that required to inhibit plant cellulose biosynthesis, our work for the first time demonstrates that a cellulose biosynthesis inhibitor affects fungal growth, changes fungal morphology and expression of genes connected to fungal cell wall biosynthesis.